STRUKTUR MIKRO KOMPOSIT HYDROXYAPATI/KITOSAN YANG DIINFILTRASI CYANOACRYLATE - Purnomo -; Endang Tri Wahyuni Maharani (Universitas Muhammadiyah Semarang, 2014)
Brittle nature of hydroxyapatite (HA) for bone implants reduced by adding chitosan (K). To strengthen the particles bond of the composite, cyanoacrylate infiltrated into the composites.Infiltration performed at room temperature and without any external pressure treatment system.The purpose of this study is to examine the microstructure of hydroxyapatite-chitosan composite by the presence infitrasi cyanoacrylate. The aim of this study is to examine the microstructure of hydroxyapatite-chitosan composite by infiltration of cyanoacrylate. Surface morphology observed by SEM on the specimen showed that the higher the content of chitosan, cyanoacrylateincreasingly looks much infiltrated composite hydroxyapatite-chitosan.